Ke Arah Arkeologi Islam: Uka Tjandrasasmita & Hasan Muarif Ambary - Widyanti Herdyaningrum (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2018)
Archeology is one science that is very close - even sticky - to history, because both aim at the same: reveal human life in the past. History is based more on written data, while archeology on sources in the form of objects or artifacts obtained, among others, through excavation. History is relatively free to take archaeological findings to strengthen certain arguments in the history of history in the early days as well as afterwards. This can be seen from the early history of Islam in Indonesia which also relies on archaeological findings. Islamic Archeology tries to systematically examine the abandoned material data and explains how cultural diversity in an area can produce a high civilization while forming the center of Islamic civilization, especially in Indonesia. Discussion of Islamic Archeology through Uka Tjandrasasmita and Hasan Muarif Ambary became important for the development of Islamic culture and development in Indonesia